Judicial Consistency and Sentencing Disparity in Military Narcotics Cases: Evidence from Indonesian Military Courts - Dhini Aryanti; Ismail Koto (Abdurrauf Law and Sharia, 2026)
Narcotics abuse is one of the serious violations as stated in the Telegram Letter of the Commander of the Indonesian Armed Forces Number ST/398/2009 dated July 22, 2009 and the Telegram Letter of the Commander of Kodam I/Bukit Barisan Number STR/25/2007 dated January 27, 2007 and is a criminal offense regulated in the Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics article 127 Paragraph (1) letter a,  has a bad effect and can damage the discipline of soldiers in their units so that it can affect the implementation of their main duties as TNI Soldiers is also contrary to the government's program which is currently intensively eradicating illicit circulation and narcotics abuse. This study aims to analyze juridically the comparison between Supreme Court Decision Number 98 K/Mil/2025 and Decision Number 391 K/Mil/2024, with a focus on the regulation of Military Criminal Law, differences in the application of law, judges' considerations, and its implications for the consistency of criminal law enforcement within the Military Court. The method used is a normative approach with a comparative method, using secondary data in the form of laws and regulations, court decisions, and related literature. The results of the study showed that there was a disparity in sanctions even though the type of criminal acts committed were the same, where the factors of the defendant's role when consuming narcotics, how many times the defendant had consumed narcotics, the adverse influence on discipline and the implementation of duties in the unit, and the judge's moral considerations were the main differentiators. The conclusion of the study emphasizes the need for standard guidelines within the Military Justice to ensure legal certainty and a sense of justice for all TNI Soldiers [Penyalahgunaan narkotika merupakan salah satu pelanggaran berat sebagaimana ditegaskan dalam Surat Telegram Panglima Tentara Nasional Indonesia Nomor ST/398/2009 tanggal 22 Juli 2009 dan Surat Telegram Panglima Kodam I/Bukit Barisan Nomor STR/25/2007 tanggal 27 Januari 2007. Selain itu, perbuatan tersebut merupakan tindak pidana yang diatur dalam Undang-Undang Republik Indonesia Nomor 35 Tahun 2009 tentang Narkotika, khususnya Pasal 127 ayat (1) huruf a. Penyalahgunaan narkotika berdampak buruk terhadap disiplin prajurit di satuan, sehingga dapat memengaruhi pelaksanaan tugas pokok sebagai prajurit TNI. Perbuatan tersebut juga bertentangan dengan program pemerintah yang saat ini secara intensif melakukan pemberantasan peredaran gelap dan penyalahgunaan narkotika. Penelitian ini bertujuan untuk menganalisis secara yuridis perbandingan antara Putusan Mahkamah Agung Nomor 98 K/Mil/2025 dan Putusan Nomor 391 K/Mil/2024, dengan fokus pada pengaturan hukum pidana militer, perbedaan penerapan hukum, pertimbangan hakim, serta implikasinya terhadap konsistensi penegakan hukum pidana di lingkungan Peradilan Militer. Metode yang digunakan adalah pendekatan normatif dengan metode perbandingan, menggunakan data sekunder berupa peraturan perundang-undangan, putusan pengadilan, dan literatur yang relevan. Hasil penelitian menunjukkan adanya disparitas pemidanaan meskipun jenis tindak pidana yang dilakukan sama. Faktor-faktor yang menjadi pembeda utama meliputi peran terdakwa dalam penggunaan narkotika, frekuensi penggunaan narkotika oleh terdakwa, pengaruh negatif terhadap disiplin dan pelaksanaan tugas di satuan, serta pertimbangan moral hakim. Kesimpulan penelitian menegaskan perlunya pedoman yang lebih terstandarisasi dalam sistem Peradilan Militer guna menjamin kepastian hukum dan mewujudkan rasa keadilan bagi seluruh prajurit TNI.]